Physicochemical properties of two varieties of rambutan (Nephelium lappaceum L.) fruit - Chai, K. F.; Karim, Roselina; Mohd Adzahan, Noranizan; Rukayadi, Yaya; Mohd Ghazali, Hasanah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Rambutan (Nephelium lappaceum L.) is an exotic fruit which is native of Southeast Asia. It is normally consumed fresh, canned or processed. Although many rambutan varieties or clones have been registered, the physicochemical properties of their fruit pulp, especially the underutilized wild types remained unknown. It is important to study the characteristics of the fruit prior transforming it into various products. Hence, this study was carried out to determine the physicochemical properties of fruit pulp from a registered clone (R7) of rambutan and a wild type rambutan. Results showed that Clone R7 comprised 58.4±2.4 % peel, 22.5±2.1 % pulp and 19.1±3.2 % seed while the wild type was made up of 55.4±3.4 % peel, 27.5±1.3 % pulp and 17.1±3.1 % seed. The pulp-to-seed ratio of the wild type (5:3) variety was significantly (p<0.05) higher than that of Clone R7 (5:4). The pH value, titratable acidity and total soluble solids of Clone R7 and wild type were pH 5.15±0.04 and 4.55±0.17, 0.11±0.01 and 0.27±0.02 % expressed as citric acid, and 14.17±0.41 and 16.33±0.82 °Brix, respectively. HPLC analysis showed that Clone R7 and wild type rambutan contained high amounts of sugars which were mainly contributed by sucrose (5.39±1.24 % for Clone R7 and 7.74±1.17 % for wild type), fructose (2.34±0.34 % for Clone R7 and 2.48±0.21 % for wild type) and glucose (2.05±0.35 % for Clone R7 and 2.25±0.20 % for wild type). The major organic acid found in the rambutan pulp was citric acid (0.29±0.06 g/100 g for Clone R7 and 0.53±0.06 g/100 g for wild type), followed by lactic, ascorbic, acetic, malic and tartaric acids. The present study suggested that the high organic acid contents in the wild type could mask its sweet flavor and give a more sour taste compared to the Clone R7.